Effects of Lacticaseibacillus paracasei K56 on perceived stress among pregraduate students: a double-blind, randomized, placebo-controlled trial - Guan, Yiran; Zhu, Ruixin; Zhao, Wen; Wang, Langrun; You, Li; Zeng, Zhaozhong; Jiang, Qiuyue; Zhu, Zeyang; Gou, Jiayu; Zhang, Qi; Guo, Jie; Li, Keji; et al. (Frontiers in Nutrition, 2025)
BackgroundGlobally, master’s and doctoral students, especially pregraduate students, are under great pressure. Probiotics are emerging as a promising intervention to improve mental health via gut-brain axis.ObjectiveThe aim of this study was to explore the impact of Lacticaseibacillus paracasei K56 supplementation on perceived stress among pregraduate students.MethodsWe conducted a double-blind, randomized, placebo-controlled trial in 120 healthy master’s and doctoral students who faced graduation. Participants were randomly assigned to either probiotics (containing Lacticaseibacillus paracasei K56 6 × 1010 CFU / d) or placebo group for 2 weeks intervention. The main outcome was perceived stress assessed using Cohen’s Perceived Stress Scale-10 (PSS-10). The secondary outcomes were stress, depression, and anxiety assessed by Depression, Anxiety and Stress Scales (DASS), gastrointestinal symptoms, and sleep evaluated by corresponding scales. These outcomes were assessed at baseline, 1, and 2 weeks. Pre- and post-treatment serum biomarkers, gut microbiota composition and metabolites were also detected.ResultsThere was no difference in changes of PSS-10 scores from baseline to 2 weeks between the K56 groups and the placebo [mean (standard error): −1.68 (0.48) vs. -0.39 (0.46), p = 0.055]. Furthermore, the K56 group exhibited superior reductions in both stress [−2.15 (0.38) vs. -0.96 (0.49), p = 0.035] and anxiety symptoms [−1.54 (0.32) vs. 0.53 (0.43), p = 0.003] via DASS compared with the placebo group. Additionally, those receiving K56 also experienced improved sleep quality (p = 0.010) and elevated levels of serotonin (5-HT) (p = 0.038) compare to placebo group. Moreover, taking probiotics K56 could modulate the pressure-induced changes in gut microbiota composition, particularly by increasing the beneficial bacteria (Lacticaseibacillus and Lacticaseibacillus paracasei), while suppressing suspected pathogenic bacteria (Shieglla and Escherichia_coli). Metabolomic analysis revealed an increased in metabolites, especially butyric acid in the K56 group (p = 0.035). Notably, there was a significant negative correlation between relative abundance of lactobacillus and stress-related symptoms, whereas butyric acid showed a significant positive correlation with lactobacillus abundance level.ConclusionThis study suggested the potential benefits of K56 supplementation in alleviating stress and significant effect in reducing anxiety and insomnia among master’s and doctoral students, which may be attributed to K56-induced changes in microbial composition and butanoate metabolism.Clinical trial registrationChictr.org.cn, identifier ChiCTR2300078447.